Binder-free carbonized bacterial cellulose-supported ruthenium nanoparticles for Li–O2 batteries. Issue 34 (27th March 2015) - Tong, Shengfu; Zheng, Mingbo; Lu, Yong; Lin, Zixia; Zhang, Xueping; He, Ping; Zhou, Haoshen
Abstract : Network structured carbonized bacterial cellulose-supported Ru nanoparticles (CBC/Ru), which provide sufficient space for Li2 O2 deposition without a significant volume effect and improve the transport of oxygen and electrons, were used as the binder-free oxygen electrode in a Li–O2 battery. Abstract : Network structured carbonized bacterial cellulose-supported Ru nanoparticles (CBC/Ru), which provide sufficient space for Li2 O2 deposition without a significant volume effect and improve the transport of oxygen and electrons, were used as the binder-free oxygen electrode in a Li–O2 battery. The CBC/Ru exhibited high activities and good stability during discharge–recharge processes.